Desiccation events change the microbial response to gradients of wastewater effluent pollution. (15th March 2019) - Romero, Ferran; Sabater, Sergi; Font, Carme; Balcázar, José Luís; Acuña, Vicenç
Abstract: While wastewater treatment plant (WWTP) effluents have become increasingly recognized as a stressor for receiving rivers, their effects on river microbial communities remain elusive. Moreover, global change is increasing the frequency and duration of desiccation events in river networks, and we ignore how desiccation might influence the response of microbial communities to WWTP effluents. In this study, we evaluated the interaction between desiccation events and WWTP effluents under different dilution capacities. Specifically, we used artificial streams in a replicated regressional design, exposing first a section of the streams to a 7-day desiccation period and then the full stream to different levels of a realistic WWTP effluent dilution, from 0% to 100% of WWTP effluent proportion of the total stream flow. The microbial community response was assessed by means of high-throughput sequencing of 16S rRNA gene amplicons and quantitative PCR targeting ecologically-relevant microbial groups. Threshold Indicator Taxa Analysis (TITAN) was used, together with model fitting, to determine community thresholds and potential indicator taxa. Results show significant interactions between WWTP effluents and desiccation, particularly when sediment type is considered. Indicator taxa included members of Proteobacteria, Actinobacteria and Cyanobacteria, with abrupt changes in community structure at WWTP effluent proportion of the total flow above 50%, which is related to nutrient levels ranging 4.6–5.2 mg  N − N O 3 − L −1, 0.21–0.32 mg  P − P O 4 3 − L −1 and 7.09–9.00 mg DOC L −1 . Our work indicates that situations where WWTP effluents account for >50% of the total river flow might risk of dramatic microbial community structure changes and should be avoided. Graphical abstract: Image 1 Highlights: Interactive effects of a WWTP effluent and desiccation were evaluated. Individual and interactive effects on bacterial community were identified. Highest change in bacterial community composition at > 50% of wastewater effluent. Bacterial indicator taxa to wastewater pollution were identified.